2020
DOI: 10.1186/s12871-020-00962-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of neuromuscular reversal by sugammadex and neostigmine with 90-day mortality after non-cardiac surgery

Abstract: Background: Reversing a neuromuscular blockade agent with sugammadex is known to lessen postoperative complications by reducing postoperative residual curarization. However, its effects on 90-day mortality are unknown. Therefore, this study aimed to compare the effects of sugammadex and neostigmine in terms of 90-day mortality after non-cardiac surgery. Methods: This retrospective cohort study analyzed the medical records of adult patients aged 18 years or older who underwent non-cardiac surgery at a single te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Furthermore, because it is not a direct neuromuscular blocking agent antagonist, the reversal of NMB using neostigmine is associated with an increased incidence of postoperative atelectasis, desaturation, postoperative pulmonary complications (PPCs), and longer hospital stay [ 7 , 8 ]. In addition, PRNMB is associated with an increased risk of PPCs [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because it is not a direct neuromuscular blocking agent antagonist, the reversal of NMB using neostigmine is associated with an increased incidence of postoperative atelectasis, desaturation, postoperative pulmonary complications (PPCs), and longer hospital stay [ 7 , 8 ]. In addition, PRNMB is associated with an increased risk of PPCs [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, neostigmine has been associated with an increased risk of oxygen desaturation in the early postoperative period [ 9 , 66 ], possibly attributable to inappropriate use, with attempts to reverse deep blockade or to high doses used inappropriately for shallow NMB, which are less efficient and often lead to less complete recovery [ 67 ]. Lastly, evidence also suggests that avoidance of PPC [ 68 ] and the use of sugammadex [ 69 ] may lead to lower mortality after non-cardiac surgeries. However, as the focus of the analysis was short-term budgetary impact, these potential benefits were not captured by the current study.…”
Section: Discussionmentioning
confidence: 99%
“…One prospective observational study enrolled 3000 patients and found that 0.06 mg/kg neostigmine can increase postoperative respiratory events [ 41 ]. A recent retrospective cohort study that observed 65 702 patients suggested that 90-day mortality after non-cardiac surgery was lower in the rocuronium-sugammadex group compared to the rocuronium-neostigmine group [ 42 ]. Therefore, the optimal regimen of muscle relaxants and antagonists may reduce the risk of short-term or long-term postoperative adverse events, but more observational studies are needed.…”
Section: Discussionmentioning
confidence: 99%